The Great Reversal : How We Let Technology Take Control of the Planet - Tabachnick, David (Book collections on Project MUSE., 2012)
As the rise of technology threatens our very humanity, Tabachnick emphasizes that we still may have time to recover and develop these capacities -- but we must first decide how far we want to allow technology to determine our existence and our future.